Distinct host immune responses in recurrent vulvovaginal candidiasis and vulvovaginal candidiasis - Ge, Gai; Yang, Zhiya; Li, Dongmei; Zhang, Ning; Chen, Biao; Shi, Dongmei (Frontiers in Immunology, 2022)
Recurrent vulvovaginal candidiasis (RVVC) and vulvovaginal candidiasis (RVVC) are one of the most common gynecological infections, primarily caused by Candida species. Although risk factors of RVVC and VVC have been identified in many studies, antifungal immunological mechanisms are still not fully understood. We performed a one-year prospective study in a local hospital to monitor 98 patients clinically diagnosed with gynecological Candida infection. The results showed that 20.41% (20/98) are with RVVC, and 79.59% (78/98) patients have VVC. C. albicans accounts for 90% and 96.1% of all strains isolated collected from RVVC and VVC patients, respectively. Antifungal susceptibility testing showed no significant difference in Candida species between RVVC and VVC patients. However, the serum levels of the IFN-γ, TNF-α and IL-17F in the RVVC group were significantly lower than those of the VVC group, while IL-4, IL-6 and IL-10 were higher in the RVVC patients than VVC patients. IL-17A and IL-2 levels were comparable between the two groups. Taken together, our results suggest that the host-immune responses, especially Th1/2 immunity, may play important roles in prognosis of RVVC and VVC.